PENGARUH ALOKASI DANA DESA (ADD) TERHADAP PEMBANGUNAN FISIK DESA DAN PEMBERDAYAAN MASYARAKAT DI DESA ADAT BUALU KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Maria Yudita Diwun; Putu Ratna Windusara Putri; I Made Sujana; Dessy Widyanasari (Nusantara Hasana Journal, 2021)
The Village Fund Allocation is a fund from the Regional Revenue and Expenditure Budget given to villages. The implementation of village fund allocation based on the act is intended in two fields, namely for development and community empowerment. However, in its implementation there are still shortcomings that are owned by village officials in the field of human resources that manage and technology used by villages. Good allocation of village fund can actually improve development village. This study aims to determine the effect of village fund allocation on physical and non-physical development in the area of Desa Adat Bualu, South Kuta District, Badung Regency, Bali. This study were used a quantitative approach, with a total sampel of 96 head of family from 2.646 households with purposive sampling method. Which is used based on the source is primary data and secondary data, using Structural Equation Modeling Partial Least Square (SEM-PLS) analysis technique. The results of the research using statistical t-test showed that the t-statistic and P-Value were previously known that 1) Village fund allocation was positive and had a significant effect on the physical development of the village, which was indicated by the P-Value = 0,000 < 0,05. The results of the hypothesis test show that the t-statistic value is 11,784, which means that there is a positive influence of village fund allocation on village physical development. 2) Village fund allocation is positive and has a significant effect on community empowerment, which is indicated by the P-Value = 0,000 < 0,05. The results of the hypotests test show that the t-statistic value is 9,101 which means that there is a positive influence of village fund allocation on community empowerment. 3) Simultaneous Village Fund Allocation has a positive and significant effect on village physical development and community empowerment, which is indicated by the P-Value = 0,000 < 0,05. This means that balance is important in the development of a region, it is not olny carrying out development programs that are engeged in non-physical development, namely community empowerment. Village funds are the main capital for developing villages and prospering the community nonphysical. Better allocation of village funds will have a positive balance in village physical development and community empowerment.